Conodonts in Silurian hypersaline environments: Specialized and unexpectedly diverse - Jarochowska, Emilia; Viira, Viive; Einasto, Rein; Nawrot, Rafał; Bremer, Oskar; Männik, Peep; Munnecke, Axel (Geology, 2017)
Hypersaline environments are commonly assumed to be barren of metazoans and therefore are avoided by paleontologists, yet a number of early Paleozoic jawless vertebrate groups specialized to live in such settings. Sampling bias against restricted settings resulted in substantial underestimation of their diversity. Rare studies venturing into such environments yielded multiple new species of conodonts, suggesting that the diversity and habitat range of these hyperdiverse predators of the early oceans are equally underestimated. We describe here autochthonous conodont fauna from evaporite-bearing horizons from the middle Silurian of Estonia that provide evidence for efficient osmoregulation in this group. Based on a global compilation of coeval conodont assemblages, we show that marginal-marine, periodically emergent environments were characterized by higher conodont diversity than open-marine shallow settings. This diversity is due to a high number of species occurring in these environments only. The high degree of specialization is also reflected by the highest within-habitat variability (β diversity) in marginal settings. Most conodont species had narrow environmental niches and, unlike in marine invertebrates, extreme environments were inhabited by the most specialized taxa. Such environments represent a large proportion of early Paleozoic tropical epicratonic basins. Our analysis allows quantification of the degree to which mid-Silurian conodont diversity is underestimated as a result of sampling bias against marginal-marine settings.
Keywords: Hypersaline environments; conodonts; invertebrates; quantification; Paleozoic; diversity; beta diversity; Estonia; Silurian